Maritime border security and challenges for Indonesia - Fauzan,; Kamarulnizam Abdullah,; Mohammad Zaki Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The issue of border security had drawn much attention for being an important part of a country’s national security and sovereignty, in addition to its dynamic and complex nature. Indonesia as an archipelagic country faces many problems and challenges in its maritime border areas, in addition to the problems of unresolved state borders with its neighboring countries. Indonesia also faces various trans-boundary crime actions near the maritime border areas. This study aimed at developing a conceptual framework of maritime border security and explaining the challenges of maritime border security. This study applied the qualitative approach by focusing on secondary data. The secondary data were obtained by means of analyses of documents, books, journals, magazines, bulletins and newspaper, including internet sources that were relevant with this study. The findings of this study show that Indonesia faced dynamic and complex problems of maritime border security, not only the problems of unsettled borders with several neighboring countries, but also many trans-boundary criminal activities in its maritime border areas. The problems of overlapping regulations and institutions added up to the problems to cope with the problems of maritime border security. This study recommends that the government of Indonesia needs to intensify the border diplomacy regarding the maritime borders with the neighboring countries in order to reach delimitation agreements of its maritime border. Further, the government of Indonesia should do immediate reorganization of regulations and institutions of maritime border security to handle all forms of trans-boundary crimes.